2021
DOI: 10.1021/acs.langmuir.1c01999
|View full text |Cite
|
Sign up to set email alerts
|

Development of Three-Dimensional Nickel–Cobalt Oxide Nanoflowers for Superior Photocatalytic Degradation of Food Colorant Dyes: Catalyst Properties and Reaction Kinetic Study

Abstract: In this work, we present three-dimensional flower-like nickel−cobalt oxide (F-NCO) nanosheets developed in a facile, ecofriendly hydrothermal route to apply as photocatalysts for food colorant Allura Red AC dye removal under light illumination. Using Brunauer− Emmett−Teller analysis, it was found that the F-NCO nanosheets displayed a surface area of ∼53.65 m 2 /g and a Barrett−Joyner−Halenda pore size of ∼14 nm, which was also confirmed by the calculated crystallite size of ∼15 nm using powder X-ray diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…In order to analyze the resistive-pseudocapacitive response performance of the NiO/NiCo 2 O 4 ||N-rGO ASSHPC device, the Bode plot ( phase angle vs frequency ), as shown in the inset of Figure I has been thoroughly examined. From the Bode plot, the relaxation time constant τ 0 value (estimated using the frequency value at a phase angle of −45°) of the NiO/NiCo 2 O 4 ||N-rGO ASSHPC device is estimated to be ∼0.69 s. The significantly low τ 0 value validates rapid transition from the resistive to capacitive behavior of the device, which is again ascribed to rich electro-microstructural coherence between the NiO/NiCo 2 O 4 and N-rGO leading to insignificant interfacial resistance, high charge mobility in the NiO/NiCo 2 O 4 and N-rGO, very low resistance during charge transfer in the NiO/NiCo 2 O 4 |PVA-KOH|N-rGO assembly, and rapid pseudocapacitive response during charge storage. , …”
Section: Results and Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In order to analyze the resistive-pseudocapacitive response performance of the NiO/NiCo 2 O 4 ||N-rGO ASSHPC device, the Bode plot ( phase angle vs frequency ), as shown in the inset of Figure I has been thoroughly examined. From the Bode plot, the relaxation time constant τ 0 value (estimated using the frequency value at a phase angle of −45°) of the NiO/NiCo 2 O 4 ||N-rGO ASSHPC device is estimated to be ∼0.69 s. The significantly low τ 0 value validates rapid transition from the resistive to capacitive behavior of the device, which is again ascribed to rich electro-microstructural coherence between the NiO/NiCo 2 O 4 and N-rGO leading to insignificant interfacial resistance, high charge mobility in the NiO/NiCo 2 O 4 and N-rGO, very low resistance during charge transfer in the NiO/NiCo 2 O 4 |PVA-KOH|N-rGO assembly, and rapid pseudocapacitive response during charge storage. , …”
Section: Results and Discussionmentioning
confidence: 90%
“…48 The specific capacitance (C s /F g −1 ) values of the NiO/NiCo 2 O 4 ||N-rGO ASSHPC device have been estimated from the impedance data, using eq 8, and the corresponding C s vs f plot is presented in Figure 6I. 13,18 The energy density (E D in Wh kg −1 ) and power density (P D in W kg −1 ) of the NiO/NiCo 2 O 4 ||N-rGO ASSHPC device were evaluated under various rate (applied current density) operating conditions using the discharge current i (in mA), discharging time (Δt in h), operating potential window (ΔV in V), and total mass of electrode materials used in the pseudocapacitor device (m in g) using eqs 13 and 14. 7,11,12,23,25,29 S2 in the SI.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flowers, such as nickel-cobalt oxide nanosheets, were successfully synthesized via an ecofriendly and cost-effective hydrothermal route which showed an excellent dye-degradation performance of 94.75% towards Allura red AC dye in 10 min under UV light irradiation [ 85 ]. There has been 96.12% degradation of the dye in 100 min at a pH of 4 using chitosan-coated nickel selenide nano-photocatalyst; another group of scientists reported that they had achieved 96.99% degradation within 6 min using CuO nanosheets with NaBH 4 acting as a reducing agent [ 36 ] compared to 90.54% degradation using CuO nanorods [ 86 ].…”
Section: Mechanism Of Dye Degradation By Metal and Metal Oxide Npsmentioning
confidence: 99%
“…Antibiotics that remain in water are harmful to human health and ecosystems. Semiconductor photocatalyst technology has the merit of high efficiency and environmental protection and has become a promising method for water disinfection, , dye degradation, , and antibiotic degradation. , It is important to develop a catalyst that can effectively break down antibiotics.…”
Section: Introductionmentioning
confidence: 99%